Implementation of the use of masks to prevent respiratory diseases in pedicab and motorized becak drivers - Erlani, Erlani; Sulasmi, Sulasmi; Mulyadi, Mulyadi (SAMATA JOURNAL OF PUBLIC HEALTH SCIENCE, 2024)
The application of Personal Protective Equipment (PPE), especially masks, greatly affects the health of workers on the streets, especially pedicab and motorized becak (bentor) drivers, where masks have the ability to protect someone whose function is to isolate part or all of the body from potential hazards in the workplace. The purpose of this community service activity is to provide education in the form of counselling to pedicab and bentor drivers so that they understand and are aware of the importance of preventing respiratory diseases. The target participants of this community service activity are pedicab drivers and bentor who work along the South Veteran Road of Makassar City. The knowledge of the target audience is assessed through pre-test and post-test which are distributed before and after the delivery of the material. In accordance with the results of the pre-test and post-test recapitulation, it is known that the target does not have enough knowledge so, after delivering the material, the level of target knowledge increases by 10%. In addition to delivering materials, masks were also distributed for counselling participants. The enthusiasm of the target in applying the material obtained can be seen from the target who immediately uses the mask to work along Jalan Veteran.